PENYULUHAN PENYELESAIAN MODEL RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA ANAK MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Ramadan Tabiu; Heryanti Heryanti; Nur Intan; Jumiati Ukkas; Rizal Muchtasar (Universitas Halu Oleo, 2023)
The aim of this activity is to find out the resolution of juvenile crimes using a restorative justice approach according to Law Number 1 of 2012 concerning the Juvenile Criminal Justice System. Preparation for activities starts from determining the location to identifying legal problems in the community and then preparing outreach materials. The activity was carried out using a lecture method to the participants which was then followed by questions and answers. The activity was carried out by a community service team from the university involving students. The results of the activity were that the principles of restorative justice in the Juvenile Criminal Justice System (UU Number 11 of 2012) were strictly regulated. One form of restorative is diversion. For children who have problems with the law, the nature of punishment with criminal sanctions is as an Ultimum Remedium or as a last resort. The main means are the principles of restorative justice and/or diversion, where for children as perpetrators of criminal acts, the resolution process is carried out using restorative/diversion both within the Juvenile Criminal Justice System (Children's SPP) and outside of the Juvenile SPP. The restorative/diversion process in Children's SPP can be carried out at the investigation, prosecution, or trial stages in court provided that there must be a voluntary agreement between the victim, the perpetrator, the victim's/perpetrator's family and related parties, with the aim of jointly finding a solution that is acceptable. fair by emphasizing restoration to the original state, and not retaliation. Meanwhile, outside the Children's SPP, restorative/diversion can be carried out at any time with the same conditions as the settlement in the Children's SPP. The settlement process using the principles of restorative justice is actually the same as resolving customary crimes.